A single centre experience of treatment outcomes for Helicobacter pylori infection among inner‐city children and adolescents. (26th February 2020) - Mathews, Jubin; Malik, Preeti; Rai, Anjali; Lin, Juan; Kim, Ryung S.; Pan, Debra H.
Abstract: Aim: This study assessed treatment outcomes of Helicobacter pylori ( H pylori ) infection among inner‐city children. Methods: This was a retrospective study of patients aged 1‐21 years who underwent initial treatment for H pylori infection from 2011 to 2015. We included patients who completed 2 weeks of treatment with documented adequate compliance after H pylori infection was diagnosed. Treatment outcomes were measured based on stool H pylori antigen and/or histology. Results: Of the total 261 patients diagnosed with H pylori, 239 completed the first‐line treatment. The regimens used included amoxicillin/clarithromycin/proton pump inhibitor (PPI) in 207/239 patients (86.6%), amoxicillin/metronidazole/PPI in 14/239 patients (5.8%) and other regimens in 18/239 patients (7.5%). H pylori eradication status was tested in 111/207 (53.6%) patients treated with amoxicillin/clarithromycin/PPI, and the eradication was achieved in 84/111(75.7%) patients. The treatment success rates for amoxicillin/metronidazole/PPI and other regimens were 71.4% (5/7) and 63.6% (7/11), respectively. There was no statistical significance of post‐treatment stool H pylori antigen results between PPI (n = 31) and no PPI (n = 43) users. Conclusion: The study showed an eradication rate of 75.7% with the regimen amoxicillin/clarithromycin/PPI suggesting significant antibiotic resistance in our population. The use of PPI did not influence post‐treatment stool H pylori antigen results.